Descriptive-contrastive analysis of Ilocano and English personal pronouns - Cruz, Bernabela Tomas de la 1927- (s.n.], 1964)
This study aims to present a descriptive-contrastive analysis of Ilocano and English personal pronouns and to predict problems that might be met by Ilocano students in learning English personal pronouns.